The pursuit of happiness Does gender parity in social institutions matter? - Ferrant, Gaëlle (OECD Development Centre Working Papers, 2017)
The OECD has long argued that the ultimate goal of public policies is to improve the quality of our lives. But what makes us happy? Does living in a country guaranteeing equal rights and opportunities to women and men increase people's happiness? This paper shows that gender based discrimination in social institutions, measured by the Social Institutions and Gender Index (SIGI), impedes well-being, beyond its negative impact on economic growth and GDP. Both men and women are happier when living in a country where social institutions offer equal rights and opportunities to women and men, even when taking into account country and individual characteristics. Current gender-based discrimination in social institutions fuels a decline of 4.4% in the world average level of life satisfaction. Conversely, eliminating gender-based discrimination in social institutions could reduce the share of the "unhappy" population from 14% to 5% globally